2009
DOI: 10.1111/j.1462-2920.2008.01831.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria beneath the West Antarctic Ice Sheet

Abstract: Summary Subglacial environments, particularly those that lie beneath polar ice sheets, are beginning to be recognized as an important part of Earth's biosphere. However, except for indirect indications of microbial assemblages in subglacial Lake Vostok, Antarctica, no sub‐ice sheet environments have been shown to support microbial ecosystems. Here we report 16S rRNA gene and isolate diversity in sediments collected from beneath the Kamb Ice Stream, West Antarctic Ice Sheet and stored for 15 months at 4°C. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 36 publications
7
95
1
1
Order By: Relevance
“…The analysis of nucleic acids from SLW samples revealed three betaproteobacterial OTUs that were closely related to sequences retrieved from sediments below the KIS [18]. The closest cultured relatives to these environmental sequences included Polarmonas glacialis (5% of OTUs in SLW water and 1.8% in sediments), an aerobic heterotroph, which was also the second most abundant OTU in SLW waters [7].…”
Section: (D) a Chemosynthetic Ecosystem Below Icementioning
confidence: 82%
See 1 more Smart Citation
“…The analysis of nucleic acids from SLW samples revealed three betaproteobacterial OTUs that were closely related to sequences retrieved from sediments below the KIS [18]. The closest cultured relatives to these environmental sequences included Polarmonas glacialis (5% of OTUs in SLW water and 1.8% in sediments), an aerobic heterotroph, which was also the second most abundant OTU in SLW waters [7].…”
Section: (D) a Chemosynthetic Ecosystem Below Icementioning
confidence: 82%
“…Samples of this material contained microbial cells and offered the first evidence for deep subsurface life in Antarctica [6,16,17]. A sediment core collected from under the Kamb Ice Stream (KIS), West Antarctica, which is due north of Whillans Ice Stream (WIS), was also shown to contain viable microbial cells [18]. These authors concluded that the KIS sample was most likely enriched in cell numbers relative to expected in situ abundances due to prolonged storage at 4 • C. However, the organisms identified using nucleic acid sequencing and cultivation were unlikely to have resulted from contamination given the low porosity and hydraulic conductivity of the sediments [19].…”
Section: Antarctic Subglacial Lakes: An Underexplored Microbial Habitatmentioning
confidence: 98%
“…In spite of the in depth investigation of the structural and functional microbial diversity in frozen environments (Price, 2007;Priscu et al, 2007;Margesin & Miteva, 2011;Gunde-Cimerman et al, 2012) such as polar ice sheets and glaciers (Miteva et al, 2004, Lanoil et al, 2009Rehakova et al, 2010;Anesio & Laybourn-Parry, 2012), permafrost (Rivkina et al, 2004), mountain glacier forefields (Lapanje et al, 2012;Zumsteg et al, 2012), frozen lakes (Felip et al, 1995), sea ice (Deming, 2002), Arctic (Varin et al, 2010;Adams et al, 2014) and Antarctic permanent lake ice (Priscu et al, 1998;Dieser et al, 2010, Murray et al, 2012, very little is known about microbial communities present in cave-hosted perennial ice accumulations. Such habitats are found in caves from mid-latitude, mid-altitude mountains, where the combination of cave morphology and local climatic conditions allow for the year-round preservation of ice and associated azonal glacial climatic conditions (Perşoiu & Onac, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have described microorganisms in the seafloor (Sogin et al, 2006;Mason et al, 2010), in continental crust (Davidson et al, 2011) and beneath ice sheets (Lanoil et al, 2009). A deep microbial biosphere may be a vast reservoir of diversity (Whitman et al, 1998), a refuge for life (Sleep and Zahnle, 1998) and the setting of the origin of life itself (Martin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%